Exploring the links between emotional intelligence and writing performance among Ethiopian high school learners - Hiluf, Belete; Alemu, Marew; Gebremariam, Hailay Tesfay (Cogent education, 2024)
Emotional intelligence (EI) refers to the ability to recognize, understand, and manage emotions, which has been found to play a crucial role in academic achievement. However, there is limited research on the impact of EI on writing performance, particularly in the Ethiopian context. Therefore, this study aims to address this gap by examining the correlation between EI and writing performance among Ethiopian high school students. To achieve this objective, a correlational research design was used. A sample of 11th-grade students (aged between 17 and 24; 69 male and 107 female) from high schools in Ethiopia was selected using a simple random sampling method. The participants completed a standardized EI questionnaire, providing quantitative data. Additionally, a writing task was assigned to the participants, and their written compositions were analyzed to assess their writing performance. The collected data were analyzed for validity and reliability using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) statistics. Pearson's correlation coefficient was used to analyze the relationship between EI and writing performance, univariate analysis and ANOVA test was used to determine the difference in EI among participants. The findings of this study showed a statistically significant relationship between EI and writing performance. Furthermore, the results provided insights into the specific relationship between EI and writing performance among high school learners in Ethiopia. The implications of this study may extend to educational policy and practice, as it can inform the development of interventions and strategies to enhance students' EI and improve their writing skills.